2012
DOI: 10.1021/ja307821u
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Dynamics at a Mechanically Controllable Break Junction in Solution at Room Temperature

Abstract: The in situ observation of geometrical and electronic structural dynamics of a single molecule junction is critically important in order to further progress in molecular electronics. Observations of single molecular junctions are difficult, however, because of sensitivity limits. Here, we report surface-enhanced Raman scattering (SERS) of a single 4,4'-bipyridine molecule under conditions of in situ current flow in a nanogap, by using nano-fabricated, mechanically controllable break junction (MCBJ) electrodes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
161
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(165 citation statements)
references
References 34 publications
2
161
1
1
Order By: Relevance
“…As in previous studies (20,21,23,25,33), correlations as a function of time are observed between spectral intensity fluctuations ("blinking") and the measured conductance in the tunneling regime. Because the tunneling conductance is dominated by a molecular-scale volume at the point of closest interelectrode separation, these correlations imply few-or single-molecule Raman sensitivity.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…As in previous studies (20,21,23,25,33), correlations as a function of time are observed between spectral intensity fluctuations ("blinking") and the measured conductance in the tunneling regime. Because the tunneling conductance is dominated by a molecular-scale volume at the point of closest interelectrode separation, these correlations imply few-or single-molecule Raman sensitivity.…”
supporting
confidence: 79%
“…Plasmonic junctions between extended electrodes (19)(20)(21)(22)(23)(24)(25) show correlations of Raman response and conductance implying single-or few-molecule sensitivity, and enable studies of vibrational physics as a function of electrical bias. Spectral diffusion often is observed in singlemolecule SERS experiments (18,25,26), and there is some preliminary evidence of bias-driven mode shifts in such junctions (23), with the mechanisms of these phenomena remaining unclear.…”
mentioning
confidence: 99%
“…The mechanically controllable break junction (MCBJ) technique has been used for simultaneous measurements of SERS and conductivity [41][42][43][44][45]. Although the scanning probe technique is also available to characterize single-molecule junctions, this method is often suitable for high-speed conductance dynamics characterization during the breaking junction [27].…”
Section: Simultaneous Observation Of Sers and Conductivity Of A Singlmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) is a promising tool for detecting the interactions between molecules and localized plasmons, especially for monitoring the plasmon-induced photoexcitation process. [11][12][13][14] Based on detailed SERS measurements of an isolated single-walled carbon nanotube (SWNT) by introducing a metal nanodimer with controlled nanogap, SWNTs with certain chirality have been observed via the resonant excitation of normally forbidden transitions. 15 The newly developed extended discrete dipole approximation method showed that the highly confined electromagnetic field at the nanogap (less than 2 nm) generates an intensity gradient of the field, resulting in the excitation of higher order polarization in the direction of the radial breathing mode in the SWNT.…”
Section: ¹1mentioning
confidence: 99%